2017
DOI: 10.1021/jacs.7b09367
|View full text |Cite
|
Sign up to set email alerts
|

Dye-Sensitized Hydrobromic Acid Splitting for Hydrogen Solar Fuel Production

Abstract: Hydrobromic acid (HBr) has significant potential as an inexpensive feedstock for hydrogen gas (H) solar fuel production through HBr splitting. Mesoporous thin films of anatase TiO or SnO/TiO core-shell nanoparticles were sensitized to visible light with a new Ru polypyridyl complex that served as a photocatalyst for bromide oxidation. These thin films were tested as photoelectrodes in dye-sensitized photoelectrosynthesis cells. In 1 N HBr (aq), the photocatalyst undergoes excited-state electron injection and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 34 publications
4
71
1
Order By: Relevance
“…It can be understood that the photogenerated electrons transfer from TiO 2 to PMo 12 to form a saturated electron PMo 12 (HPB). This process produced negative current . After the electrons of PMo 12 are reached to the saturation, the PMo 12 (HPB) (absorbing visible light) and TiO 2 (absorbing ultraviolet light) will be simultaneously excited by the continuous illumination, so that the excited electrons are conducted to the external circuit to form a positive photocurrent and the photocurrent intensity is increased gradually over time, until reached the stable current.…”
Section: Resultsmentioning
confidence: 99%
“…It can be understood that the photogenerated electrons transfer from TiO 2 to PMo 12 to form a saturated electron PMo 12 (HPB). This process produced negative current . After the electrons of PMo 12 are reached to the saturation, the PMo 12 (HPB) (absorbing visible light) and TiO 2 (absorbing ultraviolet light) will be simultaneously excited by the continuous illumination, so that the excited electrons are conducted to the external circuit to form a positive photocurrent and the photocurrent intensity is increased gradually over time, until reached the stable current.…”
Section: Resultsmentioning
confidence: 99%
“…Besides alcohol oxidation, T. J. Meyer, G. J. Meyer, and their coworkers have also been investigating halide oxidation reactions as substitutes for water oxidation in a PEC . Water oxidation is a four‐electron process and poses many kinetic challenges, whereas halide oxidation reactions are just two‐electron processes and should in principle be faster.…”
Section: Pecs For Catalytic Synthesesmentioning
confidence: 99%
“…This homogeneous halide oxidation was followed by a paper on using a DSPEC for Br − oxidation (Figure b) . Brady et al .…”
Section: Pecs For Catalytic Synthesesmentioning
confidence: 99%
“…This concept had been pioneered by Meyer and co-workers, who demonstrated its potential for chloride [25] and benzyl alcohol oxidation with simultaneous H 2 evolution. [26] Others, including Sun and co-workers, [27][28][29][30] Meyer and co-workers, [31][32][33][34][35] Berlinguette and co-workers, [36][37][38] Reisner and co-workers, [14,[39][40][41] and Lei and co-workers, [42][43][44] have subsequently shown that the gap between AP and radical catalysis can potentially be bridged via the valorization of biomass, functionalization of amines, oxidation of other halides, photo-electrochemical reduction of CO 2 , and even photoreforming of plastics.…”
Section: Introductionmentioning
confidence: 99%
“…Cascade CC bond cleavage in macromolecular hydroxyl functionalized biodegradable(34)(35)(36) and non-biodegradable (37 and 38) polymers. In all the polymeric substrates, the sites of CC bond cleavage are highlighted in red, with multiple red colored CC bonds indicating the cascade shortening of the polymer chain.…”
mentioning
confidence: 99%